Stellar occultations: 10 years since the discovery of the Chariklo rings, and advances in the study of the Solar System - Ribas, Felipe Braga (Cadernos de Astronomia, 2024)
About 10 years ago, we announced the discovery of the first ring system around a Small Solar System Object. The feat was possible thanks to the use of the stellar occultation technique, which has been widely used to characterize objects in the Solar System. Its high spatial resolution allows determining the dimensions and shapes with great precision for many objects, from those close to Earth to those farthest from the Sun. In addition to the Chariklo rings discovered in 2013, rings have been identified around the dwarf planet Haumea and the trans-Neptunian object Quaoar. This shows that rings may be common in the Outer Solar System since previously imagined limits, such as the Roche Limit, do not apply to these rings. Brazilian researchers and citizen astronomers have played a fundamental role in this research, which, thanks to the LSST, may expand considerably in the coming years.
Keywords: Stellar occultation; Rings; Small Solar System Objects; Citizen Science